Anisotropic Movements in Andaman Timbers and Studies on Behaviour Pattern After Treatment - DasGupta, P. R. (Indian Forester, 1971)
The paper deals with a broad description of the anatomical and physical characteristics of Gurjan, Badam and White Chuglam which account for over 50% of the total commercial timber of Andaman islands. A comparative study has been made of the occurrence of movements in cross, radial and tangential faces in the above species. The observations indicate that during the process of drying, the pace of shrinkage in cross face when compared with shrinkage in the sides is often more significant in all species studied. When soaked in copper-chrome Arsenic and chromated-zinc chloride solutions, rate of swelling is more in these species, than their corresponding rate of swelling in cold water. But the ratio between tangential and radial directions is found to decrease on soaking with above chemicals. This is at variance with the general finding for wood which swells in chemicals. The variability in the stabilizing effect of copper-chrome-Arsenic and chromated-zinc chloride compositions on Gurjan, Badam and White Chuglam is also studied in this paper.